Mecanismos de controle do trabalho escolar em propostas de escrita narrativa em livros didáticos de português (1974-2009) - Ribeiro, Janima Bernardes (2013)
This essay aims at investigating the writing proposals of Portuguese textbooks (LDP Livros Didáticos de Português) for Middle School (EF Ensino Fundamental), from 6th to 9th grade, from the 70s to 2009. It aims to check, though the discourse reported in the Portuguese Textbook, the control directed to the practice of the teacher and the student to do in the teaching situations. Theoretically, we search for contributions that come from the Discourse Analysis of French filiation, so we can analyze the ideological constructions present in the discourse of the ―LDP‖ more specific lly the control directed to the te cher nd student the users of the book, in writing activities. It started from a corpus of 63 textbooks whereof the following steps were performed: a) mapping of the writing proposals contemplated in the ―LDP‖ of high school; b cutting in the selection of propos l ccording to the rese rch go ls intended (writing proposals of narrative texts). After mapping the writing proposals presented in the ―LDP‖ bout the criteri mentioned bove we re d the writing propos ls to ch rt the quantity of proposals of textual writing productions in each textbook (which usually follows a pattern : 12 chapters and, at the end, the writing proposal. Nevertheless, some books present 2 (two) or more writing proposals at the end of each chapter). We did a cutting in the corpus initi lly constituted 63 ―LDP‖ nd we selected 12 writing proposals of narrative texts presented in the ―LDPs‖ to present wh t we intend to n lyze. Then, we separated these proposals into two groups: 1) activities which present ―instruction guide‖ to be followed by the student; 2) writing activities that allow the student write with no need to follow a text pattern, i.e., which encourage authorship. By means of analyses, it was possible to demonstrate that, in the Basic School, generally, the writing practices concentrate, primarily, on copying activities, reproduction, rewriting and, in more advanced levels, in activities that which start from preset models, asking the students to produce text with similar themes, following the suggested structure. It is about ideals that are supposed to be followed and imitated by the students, depriving them to assume their authorship. In order to insert the student in the world of writing it s necess ry to go beyond the model of c nonic l texts pr ctice th t puts the students f r from the possibility to be ― uthors‖. In contr st to this tendency, we face, nowadays, proposals that prioritize the authorship, the creation of a style